H38 Managing communication difficulties in huntington's disease. (September 2018) - Nuzzi, Angela
Abstract : Motor speech disorder, linguistic and cognitive difficulties, and behavioral changes significantly affect communication ability in Huntington's disease. This progressive decline in communicative effectiveness negatively impacts social interactions resulting in diminished quality of life. However, these difficulties may vary over time and from person to person, requiring different intervention strategies based especially on the daily communication needs of HD patients and their families. The aims of this presentation are to: 1) highlight the need of a centered-person assessment of communication using the World Health Organization's International Classification of Functioning, Disability and Health (ICF) model; 2) overview the available speech therapy interventions in HD to support communicative abilities and participation in everyday life even in late stage. Particular attention will also be paid to the use of new technologies in Teletherapy and Augmentative and Alternative Communication (AAC).